2018
DOI: 10.1111/bjd.16254
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA methylation is associated with aggressive clinicopathological features and poor survival in cutaneous melanoma

Abstract: Aberrant methylation of TSGs is a frequent event in melanoma. It is associated with aggressive clinicopathological features and poorer survival. Epigenetic alterations may represent a significant prognostic marker with utility in routine practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…In agreement with previous studies on CM, we identified significant associations between aberrant methylation and aggressive clinicopathologic parameters in AM including the presence of lymph node metastasis, ulceration, increased mitoses, and higher Breslow thickness [21][22][23][24][25][26]. In addition, our study revealed significant correlation between aberrant methylation of HHEX, DIPK2A, NELFB/COBRA1, CDH13, TEF, IFITM1, and SIK3 and worse DSS.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In agreement with previous studies on CM, we identified significant associations between aberrant methylation and aggressive clinicopathologic parameters in AM including the presence of lymph node metastasis, ulceration, increased mitoses, and higher Breslow thickness [21][22][23][24][25][26]. In addition, our study revealed significant correlation between aberrant methylation of HHEX, DIPK2A, NELFB/COBRA1, CDH13, TEF, IFITM1, and SIK3 and worse DSS.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have revealed that promoter methylation of PTEN is an independent predictor of worse survival in melanoma [19,20]. Methylation of RARB, APC, CDH13, ESR1, CDKN2A, RASSF1, MGMT, and HOXD9 has been shown to be associated with poor survival in CM [21][22][23][24][25][26]. AMs have relatively greater prevalence of DNA methylation than other types of CM and are significantly associated with PTEN and CDH13 hypermethylation [21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To clarify the pathogenesis of MM, efforts have been focused on the identification of MM oncogenes, such as NRAS, BRAF, PTEN, MITF, NEDD9, hTERT and KIT , which have led to an improved understanding of MM etiology and opened new avenues for personalized treatment [ 5 , 6 , 7 , 8 , 9 , 10 ]. However, not only genetic deviations promote MM initiation, proliferation and progression but also epigenetic mechanisms including aberrant DNA- methylations and changes in microRNA (miR) expression, extensively reviewed elsewhere [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. The present review focuses on miR-21, which is a key oncogenic miR overexpressed in MM, glioblastoma and other common cancers of Western societies [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%